# Which of the following is a composite number? 61 , 13 , 63 , 31

Answer: It's 63, all the others are prime numbers.

## Related Questions

10) Carlos wants to mix granola and cranberries together to make trail mix. Granola costs \$3 per pound and cranberries cost \$5.50 per pound. Carlos is willing to spend \$29 and wants to make 8 pounds of trail mix. Which system of equations could Carlos use to figure out how many pounds of granola (g) and cranberries (c) she should buy?

6 pounds of granola, 2 pounds of cranberries.

Step-by-step explanation:

3g + 5.5c = 29

g + c = 8

g = 8 - c

3 * (8 - c) + 5.5c = 29

24 - 3c + 5.5c = 29

2.5c = 5

c = 2

g = 8 - c

g = 8 - 2

g = 6

Describe how to transform the graph of g(x)= ln x into the graph of f(x)= ln (3-x) -2.

The graph of g(x) = ㏑x translated 3 units to the right and then reflected

about the y-axis and then translated 2 units down to form the graph of

f(x) = ㏑(3 - x) - 2

Step-by-step explanation:

* Lets talk about the transformation

- If the function f(x) reflected across the x-axis, then the new

function g(x) = - f(x)

- If the function f(x) reflected across the y-axis, then the new

function g(x) = f(-x)

- If the function f(x) translated horizontally to the right

by h units, then the new function g(x) = f(x - h)

- If the function f(x) translated horizontally to the left

by h units, then the new function g(x) = f(x + h)

- If the function f(x) translated vertically up

by k units, then the new function g(x) = f(x) + k

- If the function f(x) translated vertically down

by k units, then the new function g(x) = f(x) – k

* lets solve the problem

∵ Graph of g(x) = ㏑x is transformed into graph of f(x) = ㏑(3 - x) - 2

- ㏑x becomes ㏑(3 - x)

∵ ㏑(3 - x) = ㏑(-x + 3)

- Take (-) as a common factor

∴ ㏑(-x + 3) = ㏑[-(x - 3)]

∵ x changed to x - 3

∴ The function g(x) translated 3 units to the right

∵ There is (-) out the bracket (x - 3) that means we change the sign

of x then we will reflect the function about the y-axis

∴ g(x) translated 3 units to the right and then reflected about the

y-axis

∵ g(x) changed to f(x) = ㏑(3 - x) - 2

∵ We subtract 2 from g(x) after horizontal translation and reflection

∴ We translate g(x) 2 units down

∴ g(x) translated 3 units to the right and then reflected about the

y-axis and then translated 2 units down

* The graph of g(x) = ㏑x translated 3 units to the right and then

reflected about the y-axis and then translated 2 units down to

form the graph of f(x) = ㏑(3 - x) - 2

c edge

Step-by-step explanation:

Solve the equation 4x squared =121

A 2.75,-2.75
B 5.5,-5.5
C 11,-11
D 30.25,-30.25

Step-by-step explanation:

4x2 =121

4x2-121=0

using the general formula

[-b( +/-) √b2-4ac]/2a

a=4, b= 0, c=-121

x= [0 ( +/-)√02-(4*4*-121)]/2.4

= ( +/-)√1936)/8 = ( +/-)5.5

x =5.5

x = -5.5

The primary goal of using correlational research is to